Electric-field alignment of aqueous multi-walled carbon nanotubes on microporous substrates. (April 2016) - Remillard, E. Marielle; Zhang, Qiaoying; Sosina, Sobambo; Branson, Zach; Dasgupta, Tirthankar; Vecitis, Chad D.
Abstract: Carbon nanotube membranes and polymer composites are used in a wide range of applications including flexible electronics, energy storage devices, and water treatment. Here, we present a method to produce a dense network of regionally aligned multi-walled carbon nanotubes (MWCNT) on the surface of microporous substrates using a combination of electric field alignment and vacuum filtration. The effect of electric field strength (0–22 Vrms mm −1 ), MWCNT concentration (0.002–0.01 wt% in water), and sample volume (0.025–0.150 mL) on the degree of alignment was examined. Qualitatively, increasing both electric field strength and MWCNT concentration resulted in an increase in differential resistance between the aligned and non-aligned directions. To quantitatively analyze the data, a statistical regression model was developed. The model indicates there is a quadratic dependence of MWCNT alignment with the strength of the electric field, MWCNT concentration, and total MWCNT mass. The best alignment within the experimental parameter space was achieved using 0.25 mL of 0.01 wt% MWCNT at an electric field strength of 22 Vrms mm −1 ; the log-ratio of resistance was 0.8.